The Effect of Discounts, Influencers, and Packaging Design on Consumer Purchase Intention for Luxcrime Cosmetics in Surabaya - Diva Istivarini; Sumainah Fauziah (Universitas KH. Abdul Chalim Mojokerto, 2025)
The beauty industry in Indonesia shows significant growth with increasingly intense competition among various cosmetic brands. Luxcrime emerges as one of the local brands that has successfully attracted attention and is favored by many Indonesian women for offering quality products at economical prices. The purpose of this study is to examine and analyze the impact of discounts, influencer use, and packaging design aspects on purchase interest for Luxcrime cosmetic products in the Surabaya area. The target group in this study is female consumers aged 18 years and above who have used and purchased Luxcrime products and reside in Surabaya. The research uses a quantitative approach with a total of 90 respondents as participants. The sampling technique applies non-probability sampling with purposive sampling method. Data analysis was conducted through multiple linear regression using IBM SPSS version 30 software to test and evaluate the data. Research findings indicate that discount factors, influencer roles, and packaging design elements have influence both individually (partially) and simultaneously on consumer interest in making purchases.